Surgeon volume and body mass index influence positive surgical margin risk after robot-assisted radical prostatectomy: Results in 732 cases. Issue 3 (3rd July 2019) - Porcaro, Antonio B.; Tafuri, Alessandro; Sebben, Marco; Corsi, Paolo; Processali, Tania; Pirozzi, Marco; Amigoni, Nelia; Rizzetto, Riccardo; Shakir, Aliasger; Cacciamani, Giovanni; Mariotto, Arianna; Brunelli, Matteo; et al.
ABSTRACT: Objectives : To evaluate clinicopathological and perioperative factors associated with the risk of focal and non-focal positive surgical margins (PSMs) after robot-assisted radical prostatectomy (RARP). Patients and methods : The study was retrospective and excluded patients who were under androgen-deprivation therapy or had prior treatments. The population included: negative SM cases (control group), focal and non-focal PSM cases (study groups). PSMs were classified as focal when the linear extent of cancer invasion was ≤1 mm and non-focal when >1 mm. The independent association of factors with the risk of focal and non-focal PSMs was assessed by multinomial logistic regression. Results : In all, 732 patients underwent RARP, from January 2013 to December 2017. An extended pelvic lymph node dissection was performed in 342 cases (46.7%). In all, 192 cases (26.3%) had PSMs, which were focal in 133 (18.2%) and non-focal in 59 (8.1%). Independent factors associated with the risk of focal PSMs were body mass index (odds ratio [OR] 0.914; P = 0.006), percentage of biopsy positive cores (BPC; OR 1.011; P = 0.015), pathological extracapsular extension (pathological tumour stage [pT]3a; OR 2.064; P = 0.016), and seminal vesicle invasion (pT3b; OR 2.150; P = 0.010). High surgeon volume was a protective factor in having focal PSM (OR 0.574; P = 0.006). Independent predictors of non-focal PSMs were BPC (OR 1, 013; P = 0, 044), pT3a (OR 4, 832; P < 0.001), and pT3b (OR 5, 153; P = 0.001). Conclusions : In high-volume centres features related to host, tumour and surgeon volume are factors that predict the risk of focal and non-focal PSMs after RARP. Abbreviations: AJCC: American joint committee on cancer; AS: active surveillance; ASA: American society of anesthesiologists; BCR: biochemical recurrence; BMI: body mass index; BPC: percentage of biopsy positive cores; ePLND: extended lymph node dissection; H&E: haematoxylin and eosin; IQR, interquartile range; ISUP: international society of urologic pathology; LNI: lymph node invasion; LOS: length of hospital stay; mpMRI: multiparametric MRI; (c)(p)N: (clinical) (pathological) nodal stage; OR: odds ratio; OT: operating time; PSA-DT: PSA-doubling time; (P)SM: (positive) surgical margin; (NS)(RA)RP: (nerve-sparing) (robot-assisted) radical prostatectomy; RT: radiation therapy; (c)(p)T: (clinical) (pathological) tumour stage